From mechanisms to anti-fibrotic drugs in hepatic stellate cell research: a global bibliometric analysis with patent and clinical perspectives (2000–2025) - Mao, Xiaowen; Chen, Peng; Wubur, Palidan; Liu, Yi; Zhao, Yuan; Zhang, Siwei; Guan, Na; Li, Bin (Frontiers in Pharmacology, 2025)
BackgroundLiver fibrosis (LF) is a progressive condition that can advance to cirrhosis and liver failure, posing a major global health burden. Hepatic stellate cells (HSCs) are central to LF pathogenesis via extracellular matrix (ECM) production and inflammatory regulation, and have been widely explored as therapeutic targets.MethodsWe searched the Web of Science Core Collection (WoSCC), Scopus, and PubMed for English-language publications using the keywords “liver fibrosis” and “stellate cells.” Additionally, ClinicalTrials.gov was queried for clinical trials, and the Innojoy search engine was used for patents. Analyses were performed using CiteSpace (version 6.2.R4), VOSviewer, R, and Microsoft Excel to examine publication trends, collaboration and citation structures, keyword co-occurrence, clustering, citation bursts, and International Patent Classification (IPC) profiles.ResultsFrom 2000 to 2025, annual publications increased from 3 to 50 (≈16.7-fold), totaling 1,042 papers; China led output (n = 672), followed by the United States (n = 162), spanning hepatology and pharmacology. Thirteen thematic clusters were identified across etiology, molecular mechanisms, and therapeutics/delivery, with targeted delivery and intervention emerging as the leading frontier. Burst terms highlighted sustained reliance on rodent in vivo models (rats/mice; carbon tetrachloride injury) alongside hepatocellular carcinoma-related signals. The patent landscape was dominated by therapeutic-use and small-molecule classes (A61P 1/16; A61K 31/), with expansion to specialized dosage forms and combination regimens (A61K 9/00; A61K 45/06) and multimodal platforms involving nucleic acids (C12N 15/113) and antibodies (C07K 16/18). Clinical trials shifted from early small molecule monotherapies to more diversified, combinable regimens.ConclusionIntegrating bibliometrics with patent and clinical landscapes, this study delineates an evolution from mechanism discovery to precision intervention in HSC - focused LF research. Future priorities include improving target/tissue specificity and advancing multimodal, patient stratified strategies to enhance translational efficiency.